Increasing Activities and Learning Outcomes of Class X MIPA-1 SMAN 1 Danau Panggang through Collaboration of 3 Kinds of Discussion Instruments with Animated Product Assignments - Noraini Noraini (research, training and philanthropy institution Natural Aceh, 2021)
low activity and student learning outcomes in a class are influenced by several factors, one of which is because the behavior and learning models used by the teacher are not yet correct in implementing a learning process. These problems can affect the activity and completeness of student learning outcomes, so there needs to be special instruments that make them more active, especially on the subject of biology which contains many scientific names such as on the subject of Plantae. The purpose of this study was to determine the collaboration of three discussion instruments with the task of learning media products in the form of power points to increase student activity and student learning outcomes of class X MIPA-1 on the subject of Plantae. This research method uses comparative descriptive analysis with a qualitative approach using simple formulas in the form of calculating averages and percentages. The results of this study indicate that the class average score is 83.64 with the completeness of learning outcomes 90.91% with this value the completeness criteria can be categorized as achieved with student activity increasing from 73.21% to 96.63% with the criteria categorized as very good